Implementation Of Genetic Algorithm In Optimization Of Subject Scheduling - Listanto Tri Utomo; Farid Wahyudi (Merdeka Malang University, 2020)
The activity of implementing teacher teaching schedules in a school is complicated. There are various aspects related to the scheduling that must be involved, among others there are schedules in which the teacher intersects with other class schedules, and the distribution of the Teaching and Learning Activities, schedule is also expected to be evenly distributed each day for each class. Therefore in this study, an application will be made that can facilitate the preparation of subject schedules automatically by implementing genetic algorithms. By making an application for preparing the schedule of subjects it is expected to facilitate and accelerate the student field in the process of making the schedule of subjects by existing resources and limitations. With this application, it is also expected to facilitate communication between teachers and students in arranging class schedules so that they can achieve optimal results at State Vocational High School 1 Malang.DOI : https://doi.org/10.26905/jeemecs.v3i2.4346